2022
DOI: 10.1097/moh.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at adipose tissue lymphatics and their markers

Abstract: Purpose of reviewLymphatic vessels are found in most tissues, with the exception of the cornea and the central nervous system. Tissues that have high exposure to antigens, such as the skin and the intestine, have especially extensive lymphatic vascular networks. Despite being densely vascularized with blood vessels, adipose tissue is poorly permeated with lymphatic vasculature. Here, we focus on the recent advances in the research on adipose tissue lymphatics and present a lymphatic-focused analysis of publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Beside abundant microvessels, the visceral adipose tissue of mice also contains a dense network of lymphatic vessels. 24 , 25 Consequently, MVF isolated from epididymal fat pads should be rich of lymphatic vessel fragments. 26 Indeed, we found that MVF contained individual LYVE-1 + lymphatic vessel fragments adjacent to the microvasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside abundant microvessels, the visceral adipose tissue of mice also contains a dense network of lymphatic vessels. 24 , 25 Consequently, MVF isolated from epididymal fat pads should be rich of lymphatic vessel fragments. 26 Indeed, we found that MVF contained individual LYVE-1 + lymphatic vessel fragments adjacent to the microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“… 23 In line with this, the visceral adipose tissue of mice contains a recently described lymphatic vascular network. 24 , 25 Therefore, MVF may not only contain ADSC but also lymphatic vessel fragments and it can be assumed that they are particularly suitable building blocks for lymphatic tissue engineering. 16 , 26 In the present study, this hypothesis was tested by investigating the lymphangiogenic effects of MVF in a murine hindlimb lymphedema model.…”
Section: Introductionmentioning
confidence: 99%
“…Podocalyxin is expressed on the luminal surface of the vasculature and is a useful marker for detecting blood and lymphatic vessels in various tissues. 2 , 3 , 4 LYVE1 is a more specific marker for mainly initial (capillary) lymphatic vessels. This protocol has also been used for other stainings using antibodies against vascular endothelial growth factor receptors 2 and 3 (KDR, FLT4), prospero homeobox protein 1 (PROX1), ETS-related gene (ERG), and vascular endothelial (VE)-cadherin (CDH5) in the adult murine small intestines.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%